(untitled) (Bangladesh Journal of Botany, 2008)
Scorzonera amasiana Hausskn. and Bornm. was described from type specimens collected by J.F.N. Bornmueller in 1889 but it was not collected again until 1993, when it was found near Amasya, Turkey. Populations of S. amasiana were quite small at that limited locations and were vulnerable to human impacts. Therefore, suitable conservation strategies should be developed immediately in order to protect the species from probable extinction. Here, an additional three small populations are reported. Brief history, morphology, habitat and ecology of this endemic species have been discussed. Its current conservation status was reevaluated with respect to the latest IUCN criteria. A key to distinguish it from the other closely related Turkish species is also provided and its distribution map is appended. Â Key words: Endangered, Rediscovery, Scorzonera, Turkey DOI = 10.3329/bjb.v36i2.1502 Bangladesh J. Bot. 36(2): 139-144, 2007 (December)